STRATEGI EZAKI GLICO Co., Ltd DALAM MEMASARKAN PRODUK ES KRIM GLICO DI INDONESIA - Klementina Silalahi; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study discusses the strategy of Ezaki Glico in marketing Glico Wings ice cream products in Indonesia. Glico is one of the largest ice cream producers in Japan and has expanded its market in the ice cream industry in Southeast Asia, one of which is Indonesia. Indonesia is the largest ice cream consuming country in Southeast Asia with a consumption volume of 158 million liters each year. The ice cream market in Indonesia is controlled by Unilever and Campina, even Unilever is called as the absolute market leader in Indonesia with a market share of 69% in 2017. Ezaki Glico as a new incomer company, must have a strategy to create competitiveness, so that it can have market share in IndonesiaThis study uses descriptive with a qualitative approach that emphasizes the disclosure of strategies made by Ezaki Glico in marketing Glico ice cream to Indonesia. Research data obtained from books, journals, official documents and websites that support the author's hypothesis. The author uses the perspective of liberalism and the level of analysis of multinational corporations (MNC) according to Patric Morgan. And the theory used in this research are theory of competitive advantage (Competitive Advantage). To gain a competitive advantage, an MNC must have a strategy. In this study, there are 3 strategies used by Ezaki Glico to gain a competitive advantage. The results show that Ezaki Glico's strategy in marketing Glico ice cream in Indonesia is, firstly, by making a strategic alliance through a joint venture with the Wings Group Indonesia. This strategy was chosen to take advantage of the strength distribution channels owned by Wings Group Indonesia. Second, marketing ice cream at low prices (cost leadership), Ezaki Glico's ice cream portfolio ranges from Rp. 1000 to Rp. 12,000. Third, target market strategy, to target consumers of various age segments, Glico doing diversify products by created 4 ice cream sub-brands. This strategy was successful enough and made Glico Wings a Challenger market in the ice cream industry in Indonesia.Key word: Liberalism, Competitive Advantage, Diversifying Product